Feed Resources Determination Based on Pollen Diversity in Trigona Bees (Trigona sp.) Colony - Abas, Muachiroh; Sucianto, Eddy Tri (Biosaintifika: Journal of Biology & Biology Education, 2020)
Trigona bees' food resources can be determined either directly based on flowering plants live closed to the nest or based on pollen diversity inside the nest. There is no study about Trogona bee's food resources determination based on pollen diversity inside the bee colony's nest. This study aimed to determine plant food resources based on pollen diversity found inside the Trigona nest. This research was conducted in Serang village, sub-district of Karangreja, Purbalingga Regency. Pollen samples were taken from flowering plants lives around the nest and those in the nest and then were prepared using the acetolysis method. The variables observed were pollen morphology, with parameters such as unit, shape, size, aperture, and ornamentation. The data obtained were analyzed descriptively. Based on pollen diversity, 43 species and 22 plant families were live around Trigonanest in Serang Village. Forty-one pollen types were found inside the Trigonas' nest, with 37 of them are identic to the pollen collected from flowers around the nest. It can be concluded that 37 species of flowering plants could be determined as food resources for the Trigona bee based on pollen diversity inside the nest. This research provides the first data about feed resources for Trigona bee in Serang Village based on pollen diversity. The results provide essential information about food resources, which is vital for the development of Trigona bee cultivation.